Fine job at the interface of Māoridom and journalism - Alan Samson (Asia Pacific Network, 2007)
In the introduction to her journalists guide to reporting Māoridom, Pou Kōrero author Carol Archie, a Pākehā and a journalist, agonises over how to describe non-Māori and comes up with 'other New Zealanders'. "Pākehā" won't do,' she says, 'because it has come to mean New Zealanders with European ancestry. 'Non- Māori' is negative and says what we're not, rather than what we are... an tauiwi (meaning foreigner) can offend those who still aren't tangata whenua but who still feel we belong to nowehere else but Aotearoa New Zealand."